A failure of proportion : non-consensual adoption in England and Wales - Davey, Samantha M (Oxford ; Hart, 2020)
"This book explores non-consensual adoption - an area of law which has sparked considerable debate amongst academics, practitioners and the judiciary nationally and internationally. The emphasis of this book is on the circumstances in which non-consensual adoption may be regarded as a proportionate measure and when less severe forms of intervention, such as long-term foster care or kinship care, may also meet children's needs while providing protection to children's rights under the European Convention on Human Rights. The book builds on existing literature on adoption law but takes the discussion in new directions, placing an emphasis on the need to closely scrutinise children's and parents' rights at all stages of the adoption process, not simply when parents appeal against the making of an adoption order. "--
Introduction -- Children's Best Interests and Children's and Parents' Rights -- Adoption Cases in the European Court of Human Rights -- Adoption Cases in the Courts in England and Wales -- Alternatives to Non-Consensual Adoption -- Conclusion
Based on author's thesis (doctoral - University of Essex, School of Law, 2016) issued under title: The proportionality of non-consensual adoption in England and Wales under S52(1)(B) of the Adoption and Children Act 2002.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Adoption -- Law and legislation -- England; Birthparents -- Legal status, laws, etc. -- England; Custody of children -- England; International and municipal law -- Great Britain; Family law; Electronic books